2021
DOI: 10.1001/jamanetworkopen.2021.37193
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Telehealth vs In-Person Visits Among Older Adults With Advanced Kidney Disease, Care Partners, and Clinicians

Abstract: This qualitative study identifies patient, care partner, and clinicians’ perceptions of the patient-centeredness, benefits, and drawbacks of telehealth compared with in-person visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 40 publications
4
75
0
3
Order By: Relevance
“…Potential solutions to mitigate these disparities include engaging care partners, investment in technology/internet, and use of telemedicine to supplement rather than supplant in‐person visits. 14 Distribution of video‐enabled tablets have previously been shown to significantly improve preference for telemedicine visits among veterans. 15 Studies examining the impact of implementation of these strategies in transplant patients and the overall population are sorely needed and may identify effective interventions to improve the accessibility and perception of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Potential solutions to mitigate these disparities include engaging care partners, investment in technology/internet, and use of telemedicine to supplement rather than supplant in‐person visits. 14 Distribution of video‐enabled tablets have previously been shown to significantly improve preference for telemedicine visits among veterans. 15 Studies examining the impact of implementation of these strategies in transplant patients and the overall population are sorely needed and may identify effective interventions to improve the accessibility and perception of telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…The key characteristics of the studies included in the review are summarized in Table 1. Overall, seven studies were included in this review; two focused on the effectiveness of telehealth [21,22], three focused on the experiences of patients and providers [23][24][25], and two focused on the use of telehealth [26,27]. Wong et al [21] conducted a pilot randomized controlled trial whereby they randomized 68 patients to the control arm (n=34) and the intervention arm (n=34).…”
Section: Resultsmentioning
confidence: 99%
“… 39 , 40 Going forward, older adults should be given a choice of whether they see their PCP in‐person or via telemedicine, especially since older adults with comorbidity and/or those who were non‐White tended to be less satisfied with telemedicine. 41 Others have found that non‐Whites may have heightened concerns about privacy and confidentiality associated with telehealth. 42 In addition, 22% of study participants reported feeling less comfortable bringing up multiple health issues during a telemedicine visit which is concerning for older adults with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%